Analisis strategi penerimaan siswa baru di madrasah ibtidaiyah muhammadiyah Cekel Gondangrejo Karanganyar - Alfian Eko Rochmawan; Nur Hidayah; Alfina Rona Aprilia (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to analyze the strategies and impacts of new student admissions at Madrasah Ibtidaiyah Muhammadiyah Cekel over the past three years. Utilizing a qualitative approach, the study involves a case study with in-depth interviews of parents, teachers, and school staff. Document analysis and participatory observation are also employed to understand the dynamics of student admissions and their impact on classroom management and educational quality. The results indicate the adaptability of the madrasah to fluctuations in student admissions, with effective strategies in maintaining balance and ensuring the quality of learning. Thus, this research provides a holistic overview of new student admission strategies and their impacts on education at Madrasah Ibtidaiyah Muhammadiyah Cekel.